Profile of High School Student’s Scientific Literacy to Support SDGs’13 (Climate Action) on the Global Warming Phenomenon - Lestari, Nurita Apridiana; Pratiwi, Winda; Uulaa, Rizki Fitri Rahima; Hariyono, Eko; Madlazim, Madlazim (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
The low level of scientific literacy skills is attributed to the lack of application of scientific literacy principles, the inability to interpret tables and graphs, and students' limited understanding of basic scientific concepts related to the SDGs'13. This research aims to analyze the scientific literacy abilities of 10th-grade students at SMAN 1 Surabaya in relation to supporting SDGs'13 on the Global Warming Phenomenon. The research method used is descriptive and mixed method approach. The research design involves an explanatory sequential design. The research findings indicate that the average score of 10th grade students at SMAN 1 Surabaya is 65.2, which falls within the satisfactory category. Factors contributing to the suboptimal scientific literacy abilities include the inadequate application of scientific literacy competencies in teaching, teacher’s not to familiarize students with scientific analysis of phenomena, and the continued use of conventional teaching methods. There is a lack of experimental activities that encourage students to engage with scientific data and produce experimental reports. Therefore, there is a need for innovative learning methods and tools, such as integrating the topic of global warming with the SDGs'13 climate action concept and implementing a problem based learning model. These approaches aim to foster critical thinking and environmental awareness among students, enabling them to address global issues and contribute to environmental preservation in the face of climate change. Ultimately, the goal is to ensure that knowledge about preventing climate change can be applied by students in their daily lives in the long term.